Foreign Experience In Waste Management And Recycling Of Secondary Raw Materials (Pedagogical Cluster-Journal of Pedagogical Developments, 2023)
The article provides an assessment of the effectiveness of the implementation of measures in the field of regulating the management of waste from the processing of secondary raw materials. Application of foreign experience in waste management and recycling of secondary raw materials in countries. The author analyzed the implementation of a project related to waste management and processing of secondary raw materials, systematized the most successful international experience in the field of regulating the management of municipal solid waste, and summarized the best foreign practices in this area.